Seasonality in Steer Feeding Profitability, Prices, and Performance - Jones, Rodney; Mintert, James; Albright, Martin L. (My University, 1997)
This publication documents recent seasonal trends in cattle performance and economic factors that influence steer feeding profitability.
C734_1997_06
Keywords: C734; Livestock; Economics; C